RELIABILITY AND USEFULNESS OF RELAXIN ASSAY KIT FOR PREGNANCY DIAGNOSIS IN FEMALE DOG - SRIDEVI, P; UMAMAGESWARI, J (The Indian Journal of Animal Reproduction, 2016)
Pregnancy diagnosis was done in 16 female dogs using relaxin assay kit. Out of these, breeding was done in nine dogs based upon the indication of luteinizing hormone (LH) surge and all were diagnosed positive for pregnancy using relaxin assay kit with 66.7% pregnancies diagnosed positive on day 24 post-LH surge. The remaining seven dogs were bred based upon predetermined dates and six out of seven dogs were diagnosed positive using the assay kit, with 66.7% diagnosed positive on days 27-28 post-breeding. In brief, relaxin test is a reliable and a quick indicat